PSENEN influences the progression of renal clear cell carcinoma by regulating the immune microenvironment and oxidative phosphorylation - Huang, Congying; Chen, Kaijie; Zhu, Siyu; Yang, Xin; Hou, Jiangang; Gu, Xuefeng (PeerJ, 2024)
Background Presenilin enhancer gamma-secretase subunit (PSENEN), the straight target of metformin, is highly expressed in several cancers. The role of PSENEN in kidney renal clear cell carcinoma (KIRC) has not been reported. Methods PSENEN expression in KIRC specimens was investigated in The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases, as well as by immunohistochemical analysis and qPCR assay. The relationship between PSENEN expression and patient survival was discussed. The biological function of PSENEN in KIRC and its correlation with immune infiltration of KIRC were then investigated, and possible cellular mechanisms were again analyzed. The effects of metformin on KIRC cell proliferation, migration and invasion were discussed in cellular experiments. Results PSENEN was found to be highly expressed in KIRC. The high PSENEN expression was an adverse factor in KIRC. Several immune-related pathways were enriched including immune response, complement and coagulation cascade reactions, and neutrophil extracellular trap formation, as evidenced by enrichment analyses. Immune infiltration analysis revealed that PSENEN expression correlated positively with regulatory T cells. Gene set variation analysis suggested that PSENEN expression correlated positively with oxidative phosphorylation. In addition, a certain concentration of metformin was found to inhibit the proliferation, migration and invasion of KIRC cells, in which PSENEN down-regulation, AMPK up-regulation and mTOR down-regulation were also observed. Conclusions PSENEN may be involved in regulating the immune microenvironment of KIRC, and oxidative phosphorylation may also be a pathway for its involvement in cancer development. PSENEN is a novel prognostic marker for KIRC.
Keywords: PSENEN (PEN2); Metformin; Kidney renal clear cell carcinoma; Prognosis; Immune microenvironment; Oxidative phosphorylation